Focal Cryoablation of Prostate: A Review - Duke K. Bahn; Paul D. Silverman (The Scientific World Journal)
Current treatment options for men with early localized prostate cancer are either some form of radical therapy or active surveillance. Radical therapy is usually associated with significant adverse effects that might jeopardize a man's quality of life. Some observers believe that PSA screening has resulted in the over diagnosis and over treatment of prostate cancer. Many men are being diagnosed with an early stage, small volume, unifocal or unilateral prostate cancer but are reluctant to accept watchful waiting or active surveillance. Focal cryoablation is the less than complete ablation of the gland with ice. Based on review of the limited amount of material available in the current literature, focal cryoablation can provide acceptable cancer control while preserving sexual potency and urinary continence. Focal cryoablation may fill a void in the therapeutic options available to patients with unifocal or unilateral prostate cancer who have a strong desire to maintain their quality of life.